Screenshots, Chats, and Voice Notes: Rethinking Evidence in Criminal Trials - Pramidazzura Alifa Rifqi; Samsidar; Harly Clifford Jonas Salmon (PT. Anagata Sembagi Education, 2026)
The increasing reliance on screenshots, chats, and voice notes in Indonesian criminal proceedings reflects a significant shift in evidentiary practices driven by digital communication technologies. However, this development has not been followed by adequate normative adaptation within criminal procedural law. Article 184 of the Criminal Procedure Code does not explicitly accommodate micro-digital evidence, while the Electronic Information and Transactions Law merely provides general recognition without specifying procedural standards for authentication and evidentiary weight. This condition creates normative ambiguity regarding the legal status, admissibility, and probative value of screenshots, chats, and voice notes, resulting in inconsistent judicial practices and potential violations of fair trial principles. This study employs normative legal research using statute, conceptual, and case approaches to analyze the position of micro-digital evidence in Indonesian criminal trials. The findings demonstrate that unverified digital evidence risks eroding the presumption of innocence, shifting the burden of proof to defendants, and undermining legal certainty. This article argues that criminal procedural law must be reformed to explicitly regulate the classification, authentication, and corroboration of micro-digital evidence in order to ensure technological adaptation without compromising due process of law and fair trial guarantees.